2015
DOI: 10.1016/j.joca.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Knee osteoarthritis patients with severe nocturnal pain have altered proximal tibial subchondral bone mineral density

Abstract: This study suggests that local subchondral bone density may have a role in elucidating OA-related pain pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 46 publications
4
25
1
Order By: Relevance
“…Synovial pro-inflammatory profile differs with characteristics of knee pain 15 Studies using new imaging techniques have demonstrated associations between pain at rest and bone attrition (37) and low bone mineral density at the proximal tibia (38) and patella (39). However, a cross sectional study, using perfusion parameters on dynamic contrast enhanced MRI, did not demonstrate any statistically significant association between tibial BML perfusion and pain (40).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Synovial pro-inflammatory profile differs with characteristics of knee pain 15 Studies using new imaging techniques have demonstrated associations between pain at rest and bone attrition (37) and low bone mineral density at the proximal tibia (38) and patella (39). However, a cross sectional study, using perfusion parameters on dynamic contrast enhanced MRI, did not demonstrate any statistically significant association between tibial BML perfusion and pain (40).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The authors stated that some patients in both groups were withdrawn from therapy at Year 1 and Year 2, but not all these withdrawn patients were excluded from study assessment 8. Additionally, the sample size for analysis at Year 2 in the low-dose group was 85 after 3 patients were withdrawn from 90 patients at Year 1.…”
mentioning
confidence: 99%
“…Third, the objective of the study was to compare the effects of an anti-inflammatory dose of fish oil with a lower dose of fish oil in knee OA 8. We fully agree with the authors that the OA joint inflammation can be partly reflected through the evaluation of bone marrow lesions by MRI, but we have no idea why the authors did not use MRI to assess synovitis, which is a hallmark of joint inflammation and closely related to joint pain and function in OA 9.…”
mentioning
confidence: 99%
“…with not a single common factor linking the symptoms with structural damage [259,260]. The pain within the joint could be due to several factors such as the presence of osteophytes, inflammation and the abnormal changes to the subchondral bone properties [260].…”
Section: Introductionmentioning
confidence: 99%
“…The pain within the joint could be due to several factors such as the presence of osteophytes, inflammation and the abnormal changes to the subchondral bone properties [260]. The major characteristic features of knee OA include changes to the thickness of the subchondral bone, bone volume fraction, and mineral density.…”
Section: Introductionmentioning
confidence: 99%